Analysis of Students' Critical Thinking Ability Through Problem-Based Learning Model: Analisis Kemampuan Berpikir Kritis Siswa Melalui Model Pembelajaran Berbasis Masalah - M. Imam Amanda Putra; Enik Setiyawati (Academia Open, 2022)
This study discusses the analysis of students' critical thinking skills through a problem-based learning model. With this, the researcher found a problem that needed to be researched. The problem is about how the results of a literature study on critical thinking skills of elementary school students through the use of problem-based learning models in science learning. This problem makes the researcher take a qualitative descriptive research approach using the literature study method. Sources of data obtained from journals, articles and other previous research. Sources of data taken in the study must be maximum within the last ten years. The results obtained from the research are that there are 15 previous studies with 35 total content of critical thinking indicators and there is relevance of the five critical thinking indicators in influencing the improvement of critical thinking skills of elementary school students through the use of problem-based learning models. Highlights: The study analyzes students' critical thinking skills through a problem-based learning model in science education. A qualitative descriptive research approach is employed, using literature studies from the past decade as the primary data source. The research reveals 15 previous studies with a total of 35 critical thinking indicators, emphasizing the relevance of five indicators in improving elementary school students' critical thinking skills through problem-based learning. Keywords: Critical thinking skills, Problem-based learning, Elementary school students, Literature study, Science learning